2013
DOI: 10.1002/cbic.201300567
|View full text |Cite
|
Sign up to set email alerts
|

Unlocked Nucleic Acids with a Pyrene‐Modified Uracil: Synthesis, Hybridization Studies, Fluorescent Properties and i‐Motif Stability

Abstract: The synthesis of two new phosphoramidite building blocks for the incorporation of 5-(pyren-1-yl)uracilyl unlocked nucleic acid (UNA) monomers into oligonucleotides has been developed. Monomers containing a pyrene-modified nucleobase component were found to destabilize an i-motif structure at pH 5.2, both under molecular crowding and noncrowding conditions. The presence of the pyrene-modified UNA monomers in DNA strands led to decreases in the thermal stabilities of DNA*/DNA and DNA*/RNA duplexes, but these dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…It was shown that UNA monomers modulate i-motif stability in a position-depending manner whereas no structural changes were observed in any case. In addition, 5-(pyren-1-yl)uracilyl UNA monomers were found to destabilize an i-motif structure at pH 5.2, both under molecular crowding and non-crowding conditions 125 .…”
Section: Effects Of Chemical Modifications On the Stabilitymentioning
confidence: 98%
“…It was shown that UNA monomers modulate i-motif stability in a position-depending manner whereas no structural changes were observed in any case. In addition, 5-(pyren-1-yl)uracilyl UNA monomers were found to destabilize an i-motif structure at pH 5.2, both under molecular crowding and non-crowding conditions 125 .…”
Section: Effects Of Chemical Modifications On the Stabilitymentioning
confidence: 98%
“…For example, the insertion of pyrene-attached 2′-deoxyadenosine nucleotide ( Py A) at 5′-end led to prominent increase of T m (+11.4°C) at pH 4.0 that was caused by the stacking interaction between Py A and the terminal hemiprotonated C–C base pair ( 38 ). However other pyrene-containing non-nucleotide inserts, uracil UNA monomer ( 39 ) and TINA ( 40 ), within the loop region were shown to destabilize iM. In turn, different porphyrin-containing nucleotide and non-nucleotide derivatives were placed into the fragment of the sequence that did not participate in iM core formation, and they provoked strong stabilization (average T m was 53°C, whereas T m of the unmodified sequence was <25°C) at pH 5.0 owing to porphyrin–porphyrin interactions ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…The thermal denaturation studies were performed following published protocols (Christensen et al 2001;Perlikova et al 2014). Melting curves of fully complementary and of one-mismatchcontaining oligonucleotide duplexes were recorded on a PerkinElmer LAMBDA 35 UV/Vis spectrometer equipment with a PTP 6 (Peltier Temperature Programmer) element (Massachusetts, USA).…”
Section: Thermal Denaturation Studiesmentioning
confidence: 99%